Improving engagement with healthcare in hepatitis C: a randomised controlled trial of a peer support intervention - Helen R. Stagg; Julian Surey; Marie Francis; Jennifer MacLellan; Graham R. Foster; André Charlett; Ibrahim Abubakar (BMC Medicine, 2019)
Abstract Background Peer support can enable patient engagement with healthcare services, particularly for marginalised populations. In this randomised controlled trial, the efficacy of a peer support intervention at promoting successful engagement with clinical services for chronic hepatitis C was assessed. Methods In London, UK, potential participants were approached through outreach services for problematic drug use and homelessness. Individuals positive for hepatitis C virus (HCV) after confirmatory testing were randomised using an online service to the intervention (peer support) or standard of care. The primary outcome of interest was successful engagement with clinical hepatitis services. The study was non-blinded. Absolute differences were calculated using a generalised linear model and the results compared to logistic regression. Results Three hundred sixty-four individuals consented to participate. One hundred one had chronic hepatitis C and were randomised, 63 to receive the intervention (peer support). A successful outcome was achieved by 23 individuals in this arm (36.5%) and seven (18.4%) receiving the standard of care, giving an absolute increase of 18.1% (95% confidence interval 1.0–35.2%, p value = 0.04). This was mirrored in the logistic regression (odds ratio 2.55 (0.97–6.70), p = 0.06). No serious adverse events were reported. Conclusions Peer support can improve the engagement of patients with chronic HCV with healthcare services. Trial registration ISRCTN24707359. Registered 19th October 2012.